2020
DOI: 10.3390/polym12081632
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Mechanical, Hydrophobicity and Thermal Properties of Chinese Fir Wood by Impregnation of Nano Silica Sol

Abstract: In this paper, a wood-SiO2 composite material was prepared via in-situ polymerization using vacuum/pressure impregnation technology using commercial scale nano silica sol and Chinese Fir (Cunninghamia lanceolate (Lamb.) Hook.). Scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), thermogravimetric analysis (TG), and water contact angle were used to study the changes in the microstructure and physical and mechanical properties of this composite. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…However, the intensities of the diffraction peaks of PS/Wood were lower than that of Pristine Wood. This difference may be attributed to the incorporation of silica in the wood matrix, as reported in previous studies [ 26 , 27 ]. The crystallinity of PA/Wood was quite close to that of Pristine Wood (46.41%), revealing a slight change in the crystalline zone of the wood.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…However, the intensities of the diffraction peaks of PS/Wood were lower than that of Pristine Wood. This difference may be attributed to the incorporation of silica in the wood matrix, as reported in previous studies [ 26 , 27 ]. The crystallinity of PA/Wood was quite close to that of Pristine Wood (46.41%), revealing a slight change in the crystalline zone of the wood.…”
Section: Resultsmentioning
confidence: 56%
“…It is green and environmentally friendly, and can penetrate wood scaffolds and form a stable silica network structure inside via gelation and drying [ 26 ]. Xu et al [ 27 ] prepared wood-SiO 2 composite by in situ polymerization using vacuum-pressure impregnation technology. The TG results showed that the treatment improved the thermal property of the composites.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, additional methods, such as small-angle X-ray or neutrons scattering (SAXS, SANS) [ 53 , 54 , 55 , 56 , 57 , 58 ], X-ray diffraction (XRD) [ 59 , 60 , 61 ], high-resolution transmission (HRTEM) and scanning (SEM) electron microscopies [ 59 , 62 ], nuclear magnetic resonance (NMR) spectroscopy with cryoporometry and relaxometry [ 15 , 63 , 64 , 65 ], differential scanning calorimetry (DSC) and thermoporometry [ 66 ], infrared spectroscopy (FTIR), thermogravimetry (TG) and thermoporometry, dielectric relaxation spectroscopy (DRS), thermally stimulated depolarization current (TSDC) and relaxometry, theoretical simulations, etc. [ 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 ] should be used. Besides the textural characteristics, the data of these methods allow one to obtain information on the materials’ behavior under different conditions, which could model real situations related to practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Nair et al (2017Nair et al ( , 2018 investigated the decay resistance of ZnO and CuO nanoparticles dispersed in propylene glycol impregnated rubber wood as well as the UV stabilization of the wood by ZnO, CeO2, and TiO2. In addition, Xu et al (2020) prepared wood-silica composites via in-situ polymerization, which considerably improved the microstructure, thermal and mechanical properties, and hydrophobicity of the wood. Li et al (2021) constructed nano-ZnO-coated veneers using common structural features of wood and nano-ZnO particles.…”
Section: Introductionmentioning
confidence: 99%